2013
DOI: 10.3177/jnsv.59.264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green-Leafy Vegetable Intake on Postprandial Glycemic and Lipidemic Responses and ^|^alpha;-Tocopherol Concentration in Normal Weight and Obese Men

Abstract: Summary Vegetable consumption has been encouraged as a component of nutritional education for obese and insulin-resistant patients. However, the benefits of vegetable intake in a therapeutic diet on postprandial glycemic and lipidemic responses have not been clarified. We studied the effects of the intake of spinach, a green-leafy vegetable rich in dietary fiber and a-tocopherol, with a fat-rich meal on postprandial glycemic and lipidemic changes. Fourteen normal weight and 10 obese men consumed three test mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Spinach thylakoids can also increase the secretion of GLP‐1, which is an incretin hormone and induces insulin secretion . The effects of spinach and thylakoids on insulin have been very inconsistent in previous studies . There were no significant differences in serum insulin in our study but an improvement in the HOMA‐IR index indicates that spinach extract ameliorated insulin resistance.…”
Section: Discussioncontrasting
confidence: 53%
“…Spinach thylakoids can also increase the secretion of GLP‐1, which is an incretin hormone and induces insulin secretion . The effects of spinach and thylakoids on insulin have been very inconsistent in previous studies . There were no significant differences in serum insulin in our study but an improvement in the HOMA‐IR index indicates that spinach extract ameliorated insulin resistance.…”
Section: Discussioncontrasting
confidence: 53%
“…A focus on the acute meal effect is important, due to the fact that in the modern world, people are increasingly found to be in a ‘postprandial’ state, resulting from increasing exposure to eating opportunities throughout the day, propagating the effects of western meals on cumulative metabolic trends [222]. Addressing these key related factors has already been shown to favourably affect postprandial outcomes [23,126,215,223,224].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, some aspects of the three axes are quite consistent with one another, as demonstrated by the composite pyramid (Figure 4). For example, vegetables being first, due to their combined contribution of high satiating potential [64], antioxidative capacity [223] and reduced glycaemic impact [224]. Further food qualities, including whole food structure and selected components e.g., fibre and phytonutrients, and recommended preparation methods such as light cooking, together with a variety of plants, herbs, olive oil and spices, all positively influence the three axes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent paper showed that hypocaloric diet and regular moderate exercise are effective in reducing oxidative stress along with weight loss in obese patients . In addition, it has been shown that consumption of green leafy vegetables, together with a fat‐rich meal, improves antioxidant defences in obese subjects : vegetable consumption has been encouraged as a component of nutritional education for obese and insulin‐resistant patients.…”
Section: Predominant Role Of Obesity/insulin Resistance In Oxidative mentioning
confidence: 99%